Tangan-tangan jahat : Melayu & ultrakiasu - Mohd. Ridhuan Tee Abdullah (Cheras, Kuala Lumpur : Utusan Publications, 2014)
Issue on political system and Islam in Malaysia.
Continues: Melayu menjadi minoriti dalam majoriti.
Includes bibliographical references (pages 243-251).
Mengandungi bibliografi : mukasurat 243-251.
In Malay.
Keywords: Islam and politics -- Malaysia; Islam and state -- Malaysia; Malays; Malaysia -- Politics and government